Rebel speak: a justice movement mixtape - Bain, Bryonn (California series in hip hop studies, 2022)
Prologue : Criminal minded : the hip hop roots of the critical race rebellion -- Track #1 : The blueprint : the radical solidarity of Dolores Huerta and Harry Belafonte -- Track #2 : Panther rising : surviving four decades in solitary confinement -- Track #3 : Harriet 2.0 : a dialogue with Susan Burton -- Track #4 : Critical justice : mass incarceration, mental health and trauma -- Track #5 : Beyond the bars : Jennifer Claypool and Wendy Staggs on life after lockdown -- Track #6 : Fight the power : Public Enemy's Chuck D fights the power, a dialogue with Alicia Virani -- Track #7 : Live from juvi : the artivism of Maya Jupiter and Aloe Blacc, a dialogue with Rosa M. Rios (aka Rosie) -- Track #8 : Trap classics : who's capitalizing on cannabis and incarceration? -- Track #9 : Sing Sing blues : reflections of a street cop turned warden -- Track #10 : Homecoming : coming home from prison in a pandemic, a dialogue with Cheyenne Michael Simpson.